Acute effect of whole-body vibration on high velocity squat and jump performance - Leonardo Lamas; Mauro Batista; Valmor Tricoli; Carlos Ugrinowitsch (2010)
The objective of this study was to assess the acute effect of whole-body vibration (WBV) on power production of the lower limbs during squat exercise and on vertical jump height. The performance of 30 strength-trained subjects was assessed during high velocity squat exercise (HVS) and countermovement vertical jump (CMJ) before and after being submitted to four different vibration protocols in a counterbalanced random manner. The HVS and CMJ assessments were performed 3 min before and 6, 9 and 12 min after the WBV interventions, and 6 min before and 9 and 15 min after the interventions, respectively. The different WBV protocols did not change relative peak or average power production during HVS and CMJ. However, time exerted a main effect, with a decrease in CMJ height at 3 min (-2%) and 15 min (-3.1%) after treatment. These results suggest that the WBV protocols employed in this study do not induce acute improvement in performance. However, this finding does not rule out the application of WBV as a useful strategy for training or warm-up routines.